Pengaruh Harga dan Kualitas Pelayanan terhadap Kepuasan Pelanggan Transportasi Bus CV. Makmur - Formaida Tambunan; Mery Lani Br Purba; Elisabet Tambunan (Mahesa Research Center, 2023)
This article aims to determine the effect of price and service quality on customer satisfaction for CV bus transportation. Prosperous. The research method used is a quantitative associative method. The population in this study were CV bus transportation customers. Makmur and the research sample was 100 respondents while the data obtained used a questionnaire with a Likert scale and was analyzed using multiple linear regression tests. The results of the research after analysis show that from a partial test it is known that the price and service quality variables have a significant and positive influence on customer satisfaction. This is proven by the fact that H1 has a t value = 2.254 > t table = 1.66 with a significance of 0.026 < 0.05, while H2 is proven by a t value of 7.548 > t table = 1.66 with a significance of 0.000 < 0.05. Furthermore, after simultaneous analysis, it shows that the price and service quality variables have a significant and positive influence on customer satisfaction. This is proven by the calculated F value = 85.768 > F table = 3.09 with a significance of 0.00 < 0.05. This study concludes that price and service quality have a partial and simultaneous effect on customer satisfaction.